On some Calcaronea (Porifera: Calcarea) from the Barents Sea and adjacent Polar Basin - Morozov, Grigori; Strelkova, Natalia (Zootaxa, 2024)
Four common calcareous sponge species from the Arctic are described. One species, Sycandra rappi Morozov sp. nov. is new to science. It differs in the complement of spicules from S. utriculus (Schmidt, 1869). In the latter case, there is an additional kind of spicule, small sickle-shaped diactines, in the distal cones; these spicules are absent in the new species. Additionally, current placement of the genus Sycandra Haeckel, 1872 in the family Grantiidae Dendy, 1892 is discussed. Sycetta asconoides (Breitfuss, 1896) has been relocated to the genus Grantia Fleming, 1828, as we found cortical triactines in the examined material, including type specimen slides. The fourth species, Grantia arctica (Haeckel, 1872), is described from the Franz Joseph Land for the first time. The biogeography of the Arctic calcareous sponges is also briefly discussed.